Formulation and Biomedical Activity of Oil-in-Water Nanoemulsion Combining Tinospora smilacina Water Extract and Calophyllum inophyllum Seeds Oil - Saki,Elnaz; Murthy,Vinuthaa; Wang,Hao; Khandanlou,Roshanak; Wapling,Johanna; Weir,Richard (Clinical, Cosmetic and Investigational Dermatology, 2023)
Elnaz Saki,1 Vinuthaa Murthy,1 Hao Wang,1 Roshanak Khandanlou,1 Johanna Wapling,2 Richard Weir3 1Faculty of Science and Technology, Charles Darwin University, Darwin, Northern Territory, Australia; 2Menzies School of Health Research, Charles Darwin University, Darwin, Northern Territory, Australia; 3Department of Industry, Tourism and Trade, Berrimah Veterinary Laboratory, Darwin, Northern Territory, AustraliaCorrespondence: Elnaz Saki, Faculty of Science and Technology, Charles Darwin University, Darwin, Northern Territory, 0909, Australia, Tel +61 42439 3238, Email elnaz.saki@cdu.edu.auIntroduction: Tinospora smilacina is a native plant used in traditional medicine by First Nations peoples in Australia to treat inflammation. In our previous study, an optimised Calophyllum inophyllum seed oil (CSO) nanoemulsion (NE) showed improved biomedical activities such as antimicrobial, antioxidant activity, cell viability and in vitro wound healing efficacy compared to CSO.Methods: In this study, a stable NE formulation combining T. smilacina water extract (TSWE) and CSO in a nanoemulsion (CTNE) was prepared to integrate the bioactive compounds in both native plants and improve wound healing efficacy. D-optimal mixture design was used to optimise the physicochemical characteristics of the CTNE, including droplet size and polydispersity index (PDI). Cell viability and in vitro wound healing studies were done in the presence of CTNE, TSWE and CSO against a clone of baby hamster kidney fibroblasts (BHK-21 cell clone BSR-T7/5).Results: The optimised CTNE had a 24 ± 5 nm particle size and 0.21± 0.02 PDI value and was stable after four weeks each at 4 °C and room temperature. According to the results, incorporating TSWE into CTNE improved its antioxidant activity, cell viability, and ability to promote wound healing. The study also revealed that TSWE has > 6% higher antioxidant activity than CSO. While CTNE did not significantly impact mammalian cell viability, it exhibited wound-healing properties in the BSR cell line ...